KOMPETENSI PEDAGOGIK GURU BTQ DI SD MUHAMMADIYAH PANDULANGAN ALABIO - Muh Haris Zubaidillah (Program Studi PGMI STAI Al Falah Banjarbaru, 2019)
The task of the teacher as an educator is not an easy profession, teaching and learning activities are very necessary for the role of a teacher and in it, the teacher is required to have competence. This study presents the BTQ Teacher Pedagogic Competence at SD Muhammadiyah Pandulangan. The type and approach of this research use field research and qualitative. The method of data collection is done through observation, interviews, and documentation. The subjects of this study were one BTQ teacher at SD Muhammadiyah Pandulangan, the object in this study was competence. Data collection techniques used in this study were observation, interviews, and documentation. The data processing techniques used are editing, data classification and data interpretation. To analyze the data, the authors used descriptive qualitative analysis techniques. The results of this study showed that BTQ teachers in SD Muhammadiyah Pandulangan (1) the ability to understand the characteristics of students was good, (2) able to make good learning planning, (3) the ability to carry out learning good but only masters a number of teaching methods and is less able to utilize existing media, (4) carrying out evaluation of learning outcomes is good. Keywords: Pedagogic Competence, BTQ Teacher, Pandulangan Alabio Elementary School Muhammadiyah